2011
DOI: 10.1016/j.cej.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Carbon coated monolith, a mesoporous material for the removal of methyl orange from aqueous phase: Adsorption and desorption studies

Abstract: a b s t r a c tThe cordierite monolith was successfully modified to carbonaceous material termed as carbon coated monolith (CCM). Surface studies showed about 65% of the total pore volume falls in mesopore range with acidic functionality dominating over the surface. Batch adsorption experiments were carried out to study the applicability of CCM for the removal of methyl orange (MO) from aqueous solution. Different parameters such as effect of MO concentration, contact time, initial pH, regeneration and desorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(68 citation statements)
references
References 39 publications
2
62
0
1
Order By: Relevance
“…41 The adsorption capacity of CM slightly increased with the increase of adsorption temperature to 60°C ( Figure 6B). Considering the apparent activation energy of MB adsorption on CM using the Arrhenius equation…”
Section: Adsorption Kinetics Of Methylene Blue (Mb)mentioning
confidence: 96%
“…41 The adsorption capacity of CM slightly increased with the increase of adsorption temperature to 60°C ( Figure 6B). Considering the apparent activation energy of MB adsorption on CM using the Arrhenius equation…”
Section: Adsorption Kinetics Of Methylene Blue (Mb)mentioning
confidence: 96%
“…Among the physical, chemical and biological methods of dye removal, oxidation (using oxidizing agents like ozone, ultraviolet [UV] irradiation, and hydrogen peroxide), membrane separation, coagulation and flocculation, and adsorption are commonly used [3,13]. However, other than the adsorption techniques, these methods have either high costs and/ or are technically complicated [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, other than the adsorption techniques, these methods have either high costs and/ or are technically complicated [14]. The adsorption method is highly preferable due to its low cost consumption, easy operation, higher efficiency, insensitivity to toxic materials and versatility [1,13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that increasing the layers is not effective for the photocatalytic process, whereas increasing the porous layer (mesoporous carbon) had a strong impact on the photocurrent. N 2 adsorption/desorption isotherms ( Figure 5) illuminated that mesoporous carbon and TiO 2 nanoparticles exhibited a typical type IV isotherm according to the IUPAC classification, 20 indicating mesopore-rich textural properties for both samples. In mesoporous carbon, a steep and sharp H1-type hysteresis loop at a high relative pressure (P/P 0 .0.6) was observed.…”
Section: Results and Discussion Characterization Of Photoanodesmentioning
confidence: 99%